ANALISIS KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MINYAK RAMBUT POMADE GATSBY PADA MAHASISWA FAKULTAS EKONOMI UNES-AAI - Yulistia, Yulistia (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2018)
This research aims to determine whether there is an influence of product quality, price, andpromotion on the decision to purchase Gatsby pomade products. The data collection method used inthis research is by using a questionnaire, which is a data collection technique that is carried out bygiving a set of questions or statements to students of the economic faculties of Unes-AAI.2017-2018who use Gatsby pomade products. The method of data analysis in this study used multiple linearregression. The results of this study indicate that: 1) Based on the t test it is known that the variablesof Product Quality, Price, and Promotion have a significant effect on Purchasing Decisions becausethe calculated t value is greater than t table and the sig value is smaller than the probability. 2) Basedon the F test it is known that the Product Quality, Price, and Promotion variables together have asignificant effect on Purchasing Decisions because the calculated F value is greater than F table andthe sig value is smaller than the probability. 3) The results of the analysis of determination obtainedthe Adjusted R Square number of 0.624. This shows the percentage of product quality variables,prices, and purchasing decisions, in explaining the variance of the Purchase Decision variable is59.8%. While the remaining 40.2% is influenced by other variables outside of this study such asbrands, places etc.